Study of Drainage Channel Planning with Building Information Modeling (BIM) Implementation in UB Forest Buntoro - Taufiqurrohman, Muhammad; Dermawan, Very; Nur Cahya, Evi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2024)
The UB Forest Buntoro area is a biodiversity conservation zone that has the potential to be developed into a tourist forest, so it is planned to build a drainage channel in each section of the road to overcome the runoff that occurs. This research aims to describe an example of the application of BIM in construction planning for drainage channels. In this study, drainage channel planning was done using AutoCAD Civil 3D and Storm and Sanitary Analysis (SSA) software. The AutoCAD Civil 3D application is used to create a road route for which drainage channels are planned, and the SSA is used to analyze the hydrology and hydraulics of the drainage channel. Based on Building Information Modeling findings, the optimal drainage channel design yielded channel dimensions of 0.4 m × 0.4 m. The main channels (RC (Right Channel) and LC (Left Channel)) are planned to use gabion material, while the culverts are planned to use u-ditch material and a construction planning cost of 1.571.818.500,00 IDR. This study intends to give an example of how Building Information Modeling (BIM) is applied in Indonesia, particularly in the area of water resources. It does this by utilizing AutoCAD Civil 3D and SSA programs to design drainage channels.